Pengaruh Fortifikasi Nanokalsium Terhadap Karakteristik Reologi Mie - Jufrinaldi, Jufrinaldi; First, Lourenty; Dias Septaningrum, Laura Ryan; Pangestuti, Kinanti; Sulistiawaty, Lilis; Faridah, F. (Jurnal Riset, Inovasi, Teknologi & Terapan, 2023)
Noodles have become a very popular food ingredient among the people. It is hoped that the addition of nano calcium powder in making noodles is a solution for people to meet their calcium needs. The purpose of this research is to see the effect of nanocalcium fortification on the rheological characteristics of noodles. The stages of this research consist of the synthesis of nanocalcium from broiler chicken bones, nanocalcium fortification of noodle dough and characterization of noodles using a texture analyzer. The results show that the addition of 0.7 grams of nanocalcium to 250 grams of noodle dough shows differences in rheological characteristics both by means of significance tests and principal component analysis.